The Whispers of Revolution: AI and the Transforming Landscape of Spoken Language Proficiency - Anggarini, Ida Fitri; Pratama, Anggi Cantika; Hidayat, Wildan Rahmat (Inspiring: English Education Journal, 2025)
Achieving spoken language proficiency in a second language (L2) has long been a challenge for learners. Traditional methods often rely on textbooks, grammar exercises, and classroom discussions, which may not adequately address the complexities of spoken interaction. As Artificial Intelligence (AI) technologies evolve, new possibilities emerge for enhancing L2 learning, particularly in the crucial area of spoken language development. This qualitative study explores the potential of AI-powered tools and platforms to promote spoken language proficiency in L2 learners. The research investigates how learners engage with interactive AI tutors, virtual language environments, and speech recognition technologies to develop fluency, accuracy, and natural communication skills. In-depth semi-structured interviews will be conducted with a diverse group of L2 learners of varying language backgrounds and proficiency levels. Participants will be recruited from universities students in Malang, Indonesia. The interviews will explore their experiences using AI-powered language learning tools, focusing on perceived benefits, challenges, and impact on spoken language skills. Thematic analysis will be employed to identify recurring themes and patterns across the interview data. This analysis will seek to understand how learners perceive the effectiveness of AI tools in improving their spoken language proficiency, the specific features they find most helpful, and any perceived limitations or challenges. The result revealed that there is growing body of research on AI-powered language learning by providing insights into the specific ways learners interact with and benefit from these technologies in terms of spoken language development. Also, the design and development of more effective AI-powered tools for L2 learning, particularly focusing on enhancing spoken language proficiency in a personalized and engaging manner.